2018
DOI: 10.1074/jbc.ra118.002404
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G protein signaling 5 restricts neutrophil chemotaxis and trafficking

Abstract: Neutrophils are white blood cells that are mobilized to damaged tissues and to sites of pathogen invasion, providing the first line of host defense. Chemokines displayed on the surface of blood vessels promote migration of neutrophils to these sites, and tissue- and pathogen-derived chemoattractant signals, including -formylmethionylleucylphenylalanine (fMLP), elicit further migration to sites of infection. Although nearly all chemoattractant receptors use heterotrimeric G proteins to transmit signals, many of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 60 publications
0
21
1
Order By: Relevance
“…Cathepsins are components of neutrophil granules, and the expression of three cathepsins (CTSC, CTSF, and CTSV) was significantly lower in carriers than in noncarriers. CD38 is important for neutrophil migration (38,39), whereas RGS5 inhibits neutrophil chemotaxis and trafficking (41). CD38 expression was lower and RGS5 was higher in carriers than in non-carriers.…”
Section: Functionmentioning
confidence: 99%
“…Cathepsins are components of neutrophil granules, and the expression of three cathepsins (CTSC, CTSF, and CTSV) was significantly lower in carriers than in noncarriers. CD38 is important for neutrophil migration (38,39), whereas RGS5 inhibits neutrophil chemotaxis and trafficking (41). CD38 expression was lower and RGS5 was higher in carriers than in non-carriers.…”
Section: Functionmentioning
confidence: 99%
“…This can adversely affect the kinetics of the signal transduction pathways (Hwang et al, 2017). Cells including neutrophils that lack an individual RGS protein typically exhibit enhanced GPCR signaling (Balenga et al, 2014;Chan et al, 2018;Kehrl, 2016;Xie et al, 2016). Furthermore, studies of the G184S mice have largely reported augmented GPCR-linked Gαi signaling (Neubig, 2015), yet past studies examining leukocyte chemoattractant receptors have largely reported diminished signaling (Cho et al, 2012;Hwang et al, 2015;Hwang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Rgs2 in mice increases neutrophil recruitment to inflamed lungs (George et al, 2017;George et al, 2018). Despite its low expression level, loss of Rgs5 in mice also leads to a more robust recruitment of neutrophils to inflamed lungs (Chan et al, 2018). In addition, purified neutrophils from these mice had exaggerated responses to CXCR2 and CXCR4 ligands (Chan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Rgs2 in mice increases neutrophil recruitment to inflamed lungs ( 12 , 13 ). Despite its low expression level, loss of Rgs5 in mice also leads to a more robust recruitment of neutrophils to inflamed lungs ( 14 ). In addition, purified neutrophils from these mice had exaggerated responses to CXCR2 and CXCR4 ligands ( 14 ).…”
Section: Introductionmentioning
confidence: 99%